MOTIVASI LANSIA DALAM MENGIKUTI SENAM DI KLINIK ANISA MEDICAL CENTER KOTA PADANG - Akhramil Azizah; Gusril Gusril; Anton Komaini (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2018)
The purpose of this research is to know the motivation of the elderly in following gymnastics clinic Anisa Medical Center the city of Padang. Type of this research is descriptive. The population in this research is the entire elderly who follow gymnastics Clinic Medical Center Anisa Padang city, that as many as 40 people. Sampling technique with total sampling where the population was made of all samples. Variable study was the motivation of the elderly. Data collection method using question form a scale Guttman with alternative answers